2019
DOI: 10.1183/13993003.00250-2019
|View full text |Cite
|
Sign up to set email alerts
|

Non-tuberculous mycobacterial pulmonary disease

Abstract: Nontuberculous mycobacterial pulmonary disease (NTM-PD) is a challenging infection which is becoming increasingly prevalent, particularly in the elderly, for reasons which are unknown. While underlying lung disease is a well-established risk factor for NTM-PD, it may also occur in apparently healthy individuals. No single common genetic or immunological defect has been identified in this group, and it is likely that multiple pathways contribute towards host susceptibility to NTM-PD which further interact with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
204
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(217 citation statements)
references
References 220 publications
(263 reference statements)
6
204
0
7
Order By: Relevance
“…Understanding host-pathogen interactions and the underlying mechanisms is vital for the development of new therapeutics against NTM infection [1,39,40]. Recent studies on the roles of the innate and acquired immune system in NTM infection have suggested that multiple pathways/factors contribute to the pathogenesis of Mabc infection and host protective immunity [1,40]. In this study, we found that activation of PPARα induced an antimicrobial response to Mabc infection in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…Understanding host-pathogen interactions and the underlying mechanisms is vital for the development of new therapeutics against NTM infection [1,39,40]. Recent studies on the roles of the innate and acquired immune system in NTM infection have suggested that multiple pathways/factors contribute to the pathogenesis of Mabc infection and host protective immunity [1,40]. In this study, we found that activation of PPARα induced an antimicrobial response to Mabc infection in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 53%
“…Mabc, a rapidly growing NTM, causes serious pulmonary infections in both immunocompetent and immunocompromised individuals [1,36,37]. Within the Mabc complex, Mabc (sensu stricto) is a clinically important species because it is the most drug-resistant NTM and is associated with a high rate of treatment failure [37,38].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…O risco de infecções disseminadas que caracterizam pacientes imunocomprometidos é bem conhecido, mas também podem acontecer com acometimento mais localizado, como por exemplo em linfonodos, pele e tecidos subcutâneos, bem como ossos e articulações, que também são alvos importantes da infecção por MNT. As infecções por MNT são um importante causa de morbidade e mortalidade, muitas vezes sob a forma de doença pulmonar progressiva 3 . Vários estudos realizados em diferentes partes do mundo indicam que as infecções por MNT são um problema emergente de saúde global.…”
unclassified